The United States Bayh-Dole Act and its Effect on University Technology Transfer - Gotkin, Joel (Munich Intellectual Property Law Center - MIPLC, 2012)
This publication discusses one of the most influential pieces of legislation relating to technology transfer in the United States: The Bayh-Dole Act. The publication discusses the history that led to the groundbreaking Act, characterizes strengths and weaknesses of the Act from an economic and a policy standpoint, and details the recent Supreme Court Stanford v. Roche case, which may carry implications to technology transfer in the future. The publication also compares technology transfer and the Bayh-Dole Act to technology transfer in other developed and developing countries, comparing and contrasting the technology transfer schemes.